Analisis Problematika Pendidik dalam Pembelajaran Daring pada Mata Pelajaran Matematika di Sekolah Menengah Pertama - Amelia Nur Laili; Dewi Ayu Akmalia; Elvara Nabilla Silmi; Siti Nailatul Ummah; Zulfi Nayyiroh; Imron Fauzi (Jayapangus Press, 2022)
Some obstacles will certainly be encountered in the online, but that is where the challenge is for teachers to face these obstacles and find the right solution to overcome the problems that occur in the midst of online. This study aims to describe the problems of educators in online learning in mathematics subjects in junior high schools. This research uses a qualitative approach with the type of library research. The qualitative approach is an approach that can be used to examine the condition of natural objects, where the researcher is the key instrument, the data analysis is qualitative. The results of this study indicate that the problems experienced by educators during online learning, especially in mathematics subjects in junior high school, are the understanding that students have of the mathematical concepts of junior high school students, the low motivation of students towards learning mathematics, especially junior high schools, attitudes from students who show negative attitudes, namely feelings of boredom, and internet quotas.